Heparin Stimulation of the Inhibition of Activated Protein C and other Enzymes by Human Protein C Inhibitor - Influence of the Molecular Weight of Heparin and Ionic Strength - Aznar, Justo; España, Francisco; Estellés, Amparo; Royo, Montserrat (Thrombosis and Haemostasis, 1996)
The ability of unfractionated (UF) heparin and low-molecular-weight heparin (LMWH) to potentiate the inhibition of fibrinolytic and coagulation factors by protein C inhibitor (PCI) was studied. Inhibition of activated protein C (APC), urokinase plasminogen activator (uPA), tissue plasminogen activator (tPA), thrombin, factor Xa (Xa), factor XIa (XIa) and plasma kallikrein (KK) by PCI was found to be dependent on the size of the polysaccharide. In general, maximal stimulation was reached with UF heparin, except in the case of KK. Differences in heparin stimulation were more pronounced for thrombin, APC, uPA, tPA and XIa, whereas inactivation of Xa by PCI was less dependent on the presence of heparin, and kallikrein showed higher potentiation with LMWH than with UF heparin. The second-order rate constants for enzyme inhibition by PCI were strongly dependent on the ionic strength, and, in general, with an ionic strength higher than 0.15 the heparin stimulation of the inhibition reactions was drastically reduced. These results may explain the large discrepancies in the literature on the effect of heparin on the stimulation of enzyme inhibition by PCI. They also show that LMWH is less efficient in stimulating the PCI inhibition of APC, uPA and tPA, which could contribute to the antithrombotic effect of these enzymes.